Policy Implementation in Resource-Scarce Political Environments: Applying Peter S. Cleaves’ Framework to Indonesia’s National Health Insurance (JKN) - Ramadani, Nada Aiyskamila; Simanjuntak, Gloria Yemima; Putri, Dewi Nopika; Tobing, Lulu Marisa Lumban; Yulika, Maya (Center for Maritime Policy Governance Studies (CMPGS), 2025)
The National Health Insurance (JKN) program represents Indonesia’s core strategy toward achieving Universal Health Coverage (UHC), yet its implementation continues to face persistent structural, financial, and political challenges. This study aims to analyze the effectiveness of JKN implementation using Peter S. Cleaves’ framework, which emphasizes four interrelated dimensions scarcity, apathy, political power, and policy problematique to explain how limited resources, weak public participation, and political dynamics shape policy outcomes. Employing a qualitative descriptive approach through a literature review method, this research synthesizes findings from policy documents, academic studies, and institutional reports relevant to JKN implementation. The results reveal that scarcity is reflected in uneven healthcare infrastructure and financial deficits, apathy arises from low public engagement and bureaucratic rigidity, and political power influences decision-making processes that prioritize short-term populism over long-term sustainability. The study also identifies policy problematiques in the form of complex administrative systems and coordination inefficiencies between healthcare levels. These interrelated factors create implementation gaps that limit the achievement of equitable and effective health services. By situating these findings within Cleaves’ theoretical model, the study contributes to refining the understanding of policy implementation in developing contexts, emphasizing that technological innovation and participatory communication can mitigate structural and political constraints. The research concludes that enhancing institutional capacity, fostering citizen participation, and promoting digital inclusivity are key strategies for improving equity, responsiveness, and sustainability in Indonesia’s national health insurance system.